2018
DOI: 10.1016/j.scitotenv.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Early life secondhand smoke exposure assessed by hair nicotine biomarker may reduce children's neurodevelopment at 2 years of age

Abstract: Exposure to secondhand smoke (SHS) can affect fetal brain development as well as subsequent neurodevelopment. This study aimed to determine the association between prenatal and postnatal SHS exposure with children's neurodevelopment at 2years of age. Among 107 mother-child pairs from a Malaysia prospective cohort, prenatal and postnatal SHS exposure was determined based on maternal and child hair nicotine concentrations. Multiple linear regressions were used to determine the association between prenatal and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 43 publications
1
38
1
Order By: Relevance
“…Furthermore, neurodevelopment was only assessed by using a questionnaire that may lack adequate psychometric properties. This may have reduced the evidence of the presented results 39 …”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, neurodevelopment was only assessed by using a questionnaire that may lack adequate psychometric properties. This may have reduced the evidence of the presented results 39 …”
Section: Resultsmentioning
confidence: 78%
“…The effects on 24‐month‐old toddlers revealed that second‐hand smoke exposure during pregnancy was associated with lower neurodevelopment 39 . Affected children showed poorer fine motor skills, for example hand and finger movements, and impaired communication skills in vocalising, listening and understanding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of multiple methylated CpG sites in CpG islands of promoters often causes stable silencing of genes, 71 although this gene silencing can also be initiated by other mechanisms. 71 The placental also serves as a sensor and transducer of environmental signals, such as prenatal exposure to tobacco, [72][73][74][75] air pollution, [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and environmental pollutants, [91][92][93][94] which have been tied to both neonatal morbidities and perinatal inflammation. Important questions remain in relation to the role of specific biological pathways in the placenta that when perturbed can lead to child health or disease.…”
Section: Mechanism 2: Disrupted Placental Programming and Neurodevelomentioning
confidence: 99%
“…The placental also serves as a sensor and transducer of environmental signals, such as prenatal exposure to tobacco, 72 75 air pollution, 76 – 90 and environmental pollutants, 91 94 which have been tied to both neonatal morbidities and perinatal inflammation. Important questions remain in relation to the role of specific biological pathways in the placenta that when perturbed can lead to child health or disease.…”
Section: Mechanism 2: Disrupted Placental Programming and Neurodevelomentioning
confidence: 99%